Ramping Up 504 Professional Development for All Types of Educators: Going Beyond Section 504 Being a Special Education Responsibility - Ortogero, Shawna P.; Glushenko, Vera; Jensen, Joan Umiokalani; Timmerman, Victoria; Barcarse, Tierney O. (Journal of the American Academy of Special Education Professionals, 2024)
Section 504 has recently been gaining more traction among parents, educators, and government officials as more Individuals with Disabilities Education Act (IDEA) ineligible students become eligible for Section 504. To alleviate Section 504 being a special education responsibility and ramp up the lack of 504 professional development efforts for educators, this study investigated the impact that a free credit-based online 504 course had on the growth of educators and their students eligible for Section 504. An adapted interconnected 504 professional development model is also introduced. A concurrent mixed method design was used for this study. Paired samples t-tests indicated that participants’ posttest scores were statistically higher than pretest scores in both actual 504 knowledge and perceived knowledge, confidence, and usefulness of Section 504 concepts. The results also revealed that the course positively impacted participants’ instructional practices and helped to boost the learning of their students eligible for 504.